Extraction of Avocado Seed Waste as a Potential Feedstock for Biodiesel Production - Mustafa, Mustafa; Ladien, Ahmad Fatrijan; Andiani, Balqis Putri; Saputri, Desi Riana; Damayanti, Damayanti; Fahni, Yunita; Auriyani, Wika Atro; Said, Aja Avriana; Sanjaya, Andri (Eksergi, 2024)
The rising interest in sustainable energy sources has spotlighted biodiesel as a promising alternative to fossil fuels. Avocado seed waste, rich in vegetable oil, presents a potential feedstock for biodiesel production. However, optimizing the extraction process to maximize oil yield and quality is crucial. This study addresses the knowledge gap concerning the impact of drying time and solvent type on oil extraction efficiency from avocado seeds. Here, we show the effects of varying drying times (2, 3, and 4 hours) and using two solvents (96% ethanol and isopropyl alcohol) on the oil yield and quality using Soxhlet extraction. Results indicate increased drying time correlates with reduced moisture content, with values of 79.94%, 63.17%, and 47.39% for 2, 3, and 4 hours, respectively. Comparatively, isopropyl alcohol exhibited a higher fatty acid content (0.718%) than 96% ethanol. The density of oil extracted with 96% ethanol (1.34 g/ml) after 3 hours of drying surpassed that of isopropyl alcohol. These findings suggest that drying time and solvent type significantly influence the extraction efficiency and quality of oil from avocado seeds, highlighting their potential as a viable biodiesel feedstock.